Teleorientation with the use of digital tools to assist dental care in a time of the COVID-19 pandemic: an integrative literature review (Research, Society and Development, 2021)
In the scope of the provision of health services, the dental office has undergone a true technological revolution, starting with the COVID-19 pandemic so that dental consultations could be maintained with the highest level of safety for professionals and patients, and this revolution passes for the constant use of digital tools and resources. The objective of this work was to identify how digital tools can assist in dental care at the time of the COVID-19 pandemic. An integrative literature review was conducted, through which 9 articles for qualitative analysis were selected from the eligibility criteria proposed in the PRISMA-ScR strategy, in the Scielo and Pubmed databases. It was noticed that the most used tools are those of instant messaging, such as Whatsapp and Telegram, and phone calls for telemonitoring and teleconsultation, and these actions were fostered by the recognition by the Federal Council of Dentistry of the use of Teleodontology as a necessary strategy for maintenance dental care. It is concluded, therefore, that the digital transformation caused by the pandemic of COVID-19 should become perennial even if the epidemiological situation becomes more controlled, providing better communication between the dentist and his patients.